The COVID-19 Pandemic in Ukraine: Process Evaluation, Opinion Analysis - Palian, Z. O.; Zolotenkova, O. I.; Savchenko, A. S. (Statistics of Ukraine, 2021)
The SARS-CoV-2 coronavirus pandemic has proved to be a real test of survival for modern humanity. The global crisis has affected not only the health care system, but also the entire social sphere. For the second year in a row, the world economy is under stress, and countries around the world are assessing and forecasting the scale of economic losses, trying to determine the size of direct and indirect demographic losses. It’s impossible to coordinate the implementation of anti-epidemic measures and disease prevention without adequate response and support from the population. And this requires an analysis of social behavior, its motivation and attitude to the relevant actions of state and local authorities. The article considers the current trends in the spread of SARS-CoV2 infection in Ukraine and in some European countries. Seasonal fluctuations and cyclical changes in the prevalence of this disease and the number of deaths caused by coronavirus are analyzed. The 7-day seasonal fluctuations are to some extent explained by the peculiarities of the initial registration of such events in Ukraine. After all, some of the test results and medical certificates of death caused by coronavirus disease are submitted to the relevant authorities with some delay. There is a multi-day registration lag after the weekend, when most instances do not work, so the input information is processed with a delay. The statistical estimates of expected daily number of infected with COVID-19 virus and deaths from this cause (data of the National Security and Defense Council of Ukraine for March-December 2020 and January 2021) are based on an analysis of these trends in the context of effectiveness of preventive measures from “quarantine in free day” up to a hard lockdown. The article provides a quantitative assessment of the population’s response to anti-epidemic measures of government agencies. Database of research comprised a series of opinion polls within the monitoring “Ukraine under quarantine” and “Assessment of Healthcare”, the sociological group “Rating” for 2020–2021. The results of the statistical analysis of psycho-emotional state of the population during the COVID-crisis showed significant differences in the responses of certain respondents groups by age, gender and place of residence. Using non-parametric methods of statistics, the level of Ukrainian population trust in international and domestic medical institutions, as well as in information coming from various sources was estimated. It turned out that respondents are almost 20 times more willing to read news from regular Internet resources than from the official website of the Ministry of Health of Ukraine and rely more on WHO data. In the perspective of further research, a statistical analysis of the demographic consequences of the spread of SARS-CoV2 infection in Ukraine is planned.